The third man: pseudo-objectivity and the voice of passivity / Thomas Hoy - Hoy, Thomas (ACRULeT, Faculty of Education & UiTM Press, 2006)
One of the hallmarks of academic language is the use of the third person. Developed as an academic register primarily in the natural sciences, it is seen as having an air of objectivity. Consequently, it has been mandated in a range of disciplines where the values of objectivity and detachment are less clear-cut. Students are issued with blanket instructions such as, “Never write in the first person.” The problem is that sometimes the nature and content of the task is such that the only appropriate and honest voice to use is the first person. I describe a number of cases I have encountered in my work as an academic skills adviser where students have been asked to respond to tasks which call primarily on their personal observations, insights and experiences. In being told to record such accounts in the third person, students are being asked to surrender their position of personal authority. The effect is corrosive; students lose confidence in themselves and their ideas. Potentially rich writing becomes bland and corporatist. I suggest a number of strategies that could give students more autonomy in their use of academic language. The choice of voice should never be totally conventional. There are times when the third person should shut up and let someone else speak.